College algebra with trigonometry - Barnett, Raymond A. (McGraw-Hill, 2001)
New edition of a text in which Barnett (author and former professor), Michael R. Ziegler and Karl E. Byleen (both professors in the mathematics, statistics, and computer science department at Marquette U.) emphasize problem solving, ideas and computational skills rather than mathematical theory. The 12 chapters omit most derivations and proofs unless their inclusion would add significant insight into a particular concept. They present concrete examples first, followed by a discussion of related general concepts and results. The included CD-ROM contains a student tutorial with extended real-world application videos, descriptive discussion, interactive diagrams, and matched problems.